Exploring Web Co-link Patterns for Business Intelligence: The Case of Two Chinese Industries - Vaughan, Liwen; Tang, Juan; Du, Jian (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
The method of Web co-link analysis for business intelligence that was successful in the international environment in previous studies was applied to the Chinese environment to analyze the business competition positions of companies in two Chinese industries. The study was able to map companies into various sectors and show their… La méthode de l’analyse co-liens web pour la veille stratégique, utilisée dans des études antérieures dans l’environnement international, a été appliquée à l’environnement chinois afin d’analyser les positions de veille stratégique des entreprises de deux industries chinoises. L’étude a mis en correspondance les entreprises dans différents secteurs et montre leur…